Professional Development of the Teacher's Personality in the System of Secondary Special Vocational Education - Hikmatovna, Samieva Shakhnoz; Shuxrataxadovich, Raxmatov; Sadullaevna, Asadova Sitora; Taxminasaidovna, Dj Urayeva; Nusratovna, Mukhtorova Zarnigor (Annals of the Romanian society for cell biology, 2021)
The concept of personality development can include several main points: - the teaching culture, which includes the development of the teacher's worldview, the creation of conditions for his life and professional self-determination, mastery of practical pedagogy, the prestige of teaching in this field, and which basically implies a general level of education of the teacher himself; - the psychology of teaching, including the development of pedagogical self-awareness of a teacher, his creative exclusive approach to teaching, manifested in methods of analysis, design, implementation and monitoring of the teaching process; - a teaching subject focused on the principles of stepwise deployment of the content of specific knowledge of the subject, as the main part of universal human life, and as a means of shaping the personality of students in their further professional activities; - The teaching process, including improving the ways of communicating information to students, monitoring the receipt of information, developing methods to ensure the effectiveness of Material and methods To achieve these theses, the professional development of the personality of the teacher is necessary, which includes the process of forming a set of professional qualities, universal values, a culture of self-education, taking into account the characteristics of the direction of pedagogical activity. [...]one of the main tasks for forming the personality of a teacher is the use of new information technologies in the learning process. [...]the user receives an intensive dialogue with the training system and a variety of forms of independent information processing activities.